Covalently linking heparin to antithrombin enhances prothrombinase inhibition on activated platelets - Stevic, Ivan; Chan, Howard H. W.; Chander, Ankush; Berry, Leslie R.; Chan, Anthony K. C. (Thrombosis and Haemostasis, 2013)
Factor (F)Xa within the prothrombinase complex is protected from inhibition by unfractionated heparin (UFH), enoxaparin and fondaparinux. We have developed a covalent antithrombin-heparin complex (ATH) with enhanced anticoagulant activity. We have also demonstrated that ATH is superior at inhibiting coagulation factors when assembled on artificial surfaces. The objective of the present study is to determine the ability of ATH vs AT+UFH to inhibit FXa within the prothrombinase complex when the enzyme complex is assembled on the more native platelet system. Discontinuous inhibition assays were performed to determine final k2-values for inhibition of FXa, FXa within the platelet-prothrombinase, or FXa within prothrombinase devoid of various components. Thrombin generation and plasma clotting was also assayed in the presence of resting/activated platelets ± inhibitors. Protection of FXa was not observed for ATH, whereas a moderate 60% protection was observed for AT+UFH. ATH inhibited platelet-prothrombinase ∼4-fold faster than AT+UFH. Relative to intact prothrombinase, rates for FXa inhibition by AT+UFH in prothrombinase complexes devoid of either prothrombin (II)/activated platelets/FVa were higher. However, inhibition by AT+UFH of prothrombinase devoid of FII yielded slightly lower rates compared to free FXa inhibition. Thrombin generation and plasma clotting was enhanced with activated platelets, while inhibition was better by ATH compared to AT+UFH, thus suggesting an overall enhanced anticoagulant activity of ATH against platelet-bound prothrombinase complexes.
Keywords: Coagulation; covalent antithrombin-heparin; heparin; platelets; prothrombinase complex